Modern Concept of Interior Design Food Court as Rebranding Form of Sustainability Design Related to the Growth of Mall (Case Study: Delicaè, Senayan City) - Salim, Polniwati (Humaniora, 2017)
The purpose of this paper was to make people aware of the new concept design of the food court that influence the ambiance and related to the attractiveness factors. The method of documentation of the interior element was done by the analysis to the food court in Senayan City. It was expected to be a comparison of the previous design before the renovation (Food Studio) in connection with the modernization and renewal of the design (Delicaè). Some design elements such as floor wall and ceiling that applied must bear a lasting impression and be an inbuilt piece of the decoration that linked to scale, style, and color. This research was potentially contributed to shopping malls attractiveness factors and their impact on shoppers’ satisfaction in shopping malls in Jakarta and outside the city. It can be concluded that updating the design is very important if the shopping malls do not want to left-behind in this modern area. The comparison has been made between old-design with the new one that is found out that people nowadays are very open-minded about design and do care about attractive things in shopping malls.